Diversity, equity, and inclusion in paleolimnology: insights from the 2022 IAL-IPA symposium - Liseth Pérez; Paula de Tezano Pinto; Paula Echeverría-Galindo; Fernanda Charqueño-Celis; Avery Cook Shinneman; Amy Myrbo; Marcela Sandra Tonello; Matthias Bücker; Mark Brenner; Helen Bennion; Julieta Massaferro (Journal of Paleolimnology, 2024)
This report provides insights into ways that paleolimnology is becoming, and can continue to be more diverse, equitable and inclusive. Ideas presented here came during the organization, and in part, out of a special session held during the Joint Meeting of the International Association of Limnogeology (IAL) and the International Paleolimnology Association (IPA), conducted virtually (27–29 April 2022) and in-person, in Bariloche, Argentina (27 November to 1 December 2022). It was the first time in 55 years that the combined IAL-IPA meeting (held separately prior to 2018) hosted a special session to address issues beyond the value of scientific information in lake sediments. That session, “Beyond just research data: the value of outreach, education, equality, and inclusion around lakes,” included topics such as Third Mission activities, i.e., the economic and social missions of universities and how they contribute to the broader community. It also addressed challenges to diversifying our Earth Science community, which is still characterized by underrepresentation of women, especially at the highest academic levels, suffers from the “parenthood effect,” which affects both women and men, and often fails to adequately support dual-career couples, especially in Europe. Efforts to enhance diversity, equity and inclusion (DEI) included: (1) a virtual IAL-IPA meeting for Early Career Researchers (ECRs), conducted months before the in-person conference in Argentina, (2) a special session on DEI challenges and values, (3) financial support for ECRs and attendees from low-income countries, (4) equitable ECR awards, (5) consideration of gender equity during plenary and oral presentations, (6) remote presentations, including both live and pre-recorded talks, (7) utilization of multiple communication platforms to disseminate information to conference participants, and organization of science-communication activities, and (8) pre- and post-conference courses and workshops. These efforts were supported by the local organizing committee and by the establishment of the first DEI Working Group. ECRs dominated the in-person Joint Meeting (200 of 300 attendees), which we view as an opportunity to promote changes in our discipline. We encourage members of our community to work collaboratively to shape diverse research groups and identify leaders who will promote more equitable and inclusive workplaces.

Holocene climate change and landscape development from a low-Arctic tundra lake in the western Hudson Bay region of Manitoba, Canada - Philip Camill; Charles E. Umbanhowar; Christoph Geiss; William O. Hobbs; Mark B. Edlund; Avery Cook Shinneman; Jeffrey A. Dorale; Jason Lynch (Journal of Paleolimnology, 2012)